CHOOSING SILENCE: EMOTIONAL AND CULTURAL REASONS FOR NON-PARTICIPATION IN EFL CLASSROOMS - Nematov, Abdullajon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This qualitative study investigates the affective and cultural factors impacting university-level EFL learners' silence․ Drawing on interviews and follow-up reflective journals from 18 university learners in Central Asia‚ the findings show that silence was a communicative strategy supported by affective factors and cultural expectations‚ as well as interactional norms negotiated by both learners and teachers․ The themes were silence as an emotion-regulation strategy‚ silence as a social‚ cultural and relational practice‚ silence as planned participation‚ and silence in terms of characteristic features of the classroom context․ These findings challenge conventional pedagogic perspectives on silence in the classroom as a manifestation of cognitive deficiency and student disengagement and contribute to the understanding of silence as a legitimate‚ culturally situated and emotion-regulated way of participating in the classroom․ This suggests the need to create more participatory‚ communicative EFL classrooms‚ reconsider measures for assessing talk‚ and design EFL classrooms that can ease a psychologically safe environment․ This qualitative study adds to the growing body of research on affect‚ identity and silence in university classrooms outside of the Western context․